The environmental cost implication of hub-hub versus hub bypass flight networks - Morrell, Peter; Lu, Cherie (Elsevier, 2007)
The increasing congestion at major hubs and the advantage to passengers of non-stop flights and faster journey times has intensified the debate on patterns of air service. At the same time the economics of highly focused networks has been challenged by the availability of very economic smaller capacity long-haul aircraft. The purpose of this research is to value the environmental costs of these two patterns of service: hub-to-hub and hub bypass. Five long-haul markets were evaluated both on a hub to hub and hub by-pass basis. These involved both transatlantic and Europe/Asia flights. It was found that the noise and emissions social cost impact of the hub by-pass networks was significantly lower than the hub to hub in all cases. The difference in environmental costs per passenger ranged between 25% and 73%, depending on the concentration of population around the airports and the degree to which the hub routing involved extra mileage. The difference increasedto a range of 56% to 113%, if a stimulation factor of 25% was applied to the non-stop market. The environmental cost saving for the non-stop flight amounted to just under 20% of the total aircraft operating costs of one of the cases considered.
Keywords: Environmental costs; aircraft noise; engine emissions; airline networks